2018
DOI: 10.1002/da.22736
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of risk factors for suicide attempts among Operation Enduring Freedom and Operation Iraqi Freedom veterans

Abstract: This prospective study identified several strong predictors of suicide attempts among OEF/OIF veterans which may be important targets for suicide prevention efforts. Further, co-occurrence of multiple risk factors was associated with markedly greater risk for suicide attempts; veterans with multiple risk factors appear to be at the highest risk among OEF/OIF veterans enrolled in VA care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 64 publications
(94 reference statements)
5
45
1
Order By: Relevance
“…This latter finding is consistent with a body of research showing that unit cohesion is a driver of positive psychological outcomes among general military personnel, including general well-being (Oliver et al, 1999), decreased risk for posttraumatic stress symptoms (Brailey, Vasterling, Proctor, Constans, & Friedman, 2007), and decreases in suicidal ideation (Kessler, Berglund, Borges, Nock, & Wang, 2005;Mitchell et al, 2012). Suicidal intent is a necessary component ASD-RELATED TRAITS, COHESION, AND SUICIDALITY IN MILITARY 13 of suicidal behavior (Silverman, Berman, Sanddal, O'Carroll, & Joiner, 2007), and evidence suggests that higher suicidal intent is predictive of future suicide attempts (Lee et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…This latter finding is consistent with a body of research showing that unit cohesion is a driver of positive psychological outcomes among general military personnel, including general well-being (Oliver et al, 1999), decreased risk for posttraumatic stress symptoms (Brailey, Vasterling, Proctor, Constans, & Friedman, 2007), and decreases in suicidal ideation (Kessler, Berglund, Borges, Nock, & Wang, 2005;Mitchell et al, 2012). Suicidal intent is a necessary component ASD-RELATED TRAITS, COHESION, AND SUICIDALITY IN MILITARY 13 of suicidal behavior (Silverman, Berman, Sanddal, O'Carroll, & Joiner, 2007), and evidence suggests that higher suicidal intent is predictive of future suicide attempts (Lee et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…We examined the interactive effects of PTSD symptoms and heavy alcohol use, opioid use, and marijuana use over the past 30 days, prospectively, on PTSD symptoms, suicidal thoughts, and suicidal behaviors over 12 months in a sample of at risk service members or veterans not engaged in behavioral health treatment. We expected to find that PTSD, heavy alcohol use, and opioid use prospectively predict PTSD symptoms as well as suicidal thoughts and behaviors (e.g., Ashrafioun et al, ; Conner et al, ; Lee et al, ). We further hypothesized that PTSD would exacerbate these effects.…”
Section: The Current Studymentioning
confidence: 99%
“…Posttraumatic stress disorder (PTSD) is the most common mental health problem in military personnel and has been identified as a risk factor for suicidal ideation and behavior (Lee et al, ; Sareen et al, ; Seal, Bertenthal, Miner, Sen, & Marmar, ). Recent meta‐analyses found that PTSD was associated with elevated suicidal ideation and attempted suicide across civilian and military samples (Krysinska & Lester, ; Panagioti, Gooding, & Tarrier, ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Among veterans, the risk of suicide is even greater in those who have been diagnosed with posttraumatic stress disorder (PTSD) and/or major depressive disorder (MDD). [3][4][5][6][7] Although the relationship between PTSD and/or MDD and suicide risk is well established, [8][9][10][11] less is known about other factors that may influence the development of suicidal ideation (SI) in veterans with these disorders. Identifying modifiable factors that contribute to the development of SI, a significant risk factor for suicide attempts, 3 in veterans with PTSD and/or MDD is thus critical to informing preventative approaches and reducing suicide risk in this vulnerable subset of the veteran population.…”
Section: Introductionmentioning
confidence: 99%